2013
DOI: 10.1111/jpy.12123
|View full text |Cite
|
Sign up to set email alerts
|

Continuous hydrogen peroxide production by organic buffers in phytoplankton culture media

Abstract: We investigated the production of hydrogen peroxide (HOOH) in illuminated seawater media containing a variety of zwitterionic buffers. Production rates varied extensively among buffers, with 4-(2-hydroxyethyl)1-piperazineethanesulfonic acid (HEPES) highest and N-Tris(hydroxymethyl)methyl-3-aminopropanesulfonic acid (TAPS) among the lowest. The rate of HOOH accumulation was remarkably consistent over many days, and increased linearly with buffer concentration, natural seawater concentration, and light level. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 39 publications
0
16
1
Order By: Relevance
“…Further, chemicals present in cultural systems are known to produce HOOH [40]. Previously, HEPES with 1-10 mM concentration in culture could generate enough HOOH to kill the axenic phytoplankter Prochlorococcus strain [40].…”
Section: Resultsmentioning
confidence: 99%
“…Further, chemicals present in cultural systems are known to produce HOOH [40]. Previously, HEPES with 1-10 mM concentration in culture could generate enough HOOH to kill the axenic phytoplankter Prochlorococcus strain [40].…”
Section: Resultsmentioning
confidence: 99%
“…4) may be due to the variability of CO 2 incorporation from flaming, as some cultures may have experienced larger-scale CO 2 inputs that resulted in pH decline if the CO 2 is not consumed by the culture. Previous studies have also found that up to 2 μmol L −1 of HOOH may be generated as a result of flaming (Morris and Zinser 2013). While it is recognized that mmol L −1 concentrations of HOOH are needed to cause cell death (Palenik et al 1991;Alam et al 2001), the 2 μmol L −1 of HOOH generated from flaming results in physiological changes during the upregulation of intracellular peroxidases (Price and Harrison 1988).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that light exposure causes photooxidation (and the inherent generation of reactive oxygen species, such as the weak acid HOOH) within a variety of media utilizing buffers such as HEPES, TAPS, Bicine, and TRIS (Morris and Zinser 2013). To determine the effects of photooxidation on media pH, 25 mL volumes of CT media were aliquoted into 50-mL glass culture tubes in triplicate for air-flame treatments.…”
Section: Consequences Of Photooxidation On Media Phmentioning
confidence: 99%
See 1 more Smart Citation
“…As discussed for decay above, components originally present in the growth medium could have contributed to the production rates measured in the two supernatant experiments. Morris and Zinser (2013) showed that H 2 O 2 production could occur by exposing zwitterionic buffers such as those used in growth media to light. However, the bacteria used in this experiment were grown in a dark incubator, and syringes used for spiked batch incubations were covered between time points.…”
Section: H 2 O 2 Production Ratesmentioning
confidence: 99%